PENANAMAN POHON MATOA DAN SEMPUR DI BANTARAN PINGGIRAN SUNGAI DESA SUKA MAKMUR KECAMATAN SIBOLANGIT - Nuri Ramadhan (LP3M STKIP MUHAMMADIYAH MUARA BUNGO, 2023)
Community service activities for lecturers are an effort to carry out one of the tri dharma tasks of higher education. This service activity aims to educate the public about the importance of protecting the environment around river basins by planting productive trees. In addition, the community can also understand the importance of reforestation to restore natural conditions, especially river banks which will be damaged due to natural and human factors. The implementation of this community service activity was carried out by providing an open green space for the elderly and the local community on May 28 2022 in the riverbank area of ​​Jl. Letjen Jamin Ginting Km 45 Gelora Kasih GBKP 100 Year Jubilee Park Complex, Suka Makmur Village, Sibolangit District, Deli Serdang Regency, North Sumatra Province. This Community Service is very beneficial for the elderly who are in the area where the tree is planted. This greening culture must be familiarized from an early age through the practice of planting trees. By frequently planting trees, it is hoped that it can increase people's awareness and love for preserving and protecting the environment, especially watersheds. With this Community Service activity, it is hoped that it will help the community to realize the importance of protecting the environment. The expected output targets from this activity are, First, provide an open green space for the elderly and the local community. Second, growing the local community's economy from the production of matoa and simpur tree seeds. Third, Improving the welfare of the surrounding community and the elderly.